Structural, Electrical and Dielectric Properties of Ternary Hybrid PMMA Composite. - Al-Khafaji, R S; Hussein, Rusul Taha (Al-Nahrain Journal of Science, 2018)
This study aims to synthesis ternary hybrid composite PMMA polymer matrix with TiO2, Al2O3 and ZrO2 as additives using casting technique. Range of weight fractions (84-92 wt %) of Poly (methyl methacrylate), fixed percentage (4%) of TiO2 and range of weight fractions (4-12 wt %) of Al2O3 and ZrO2 were used as started materials. Structure characterization was examined through XRD and AFM. Obtained micrograph revealed homogeneity structure and XRD pattern display present of crystals for ZrO2. Dielectric properties like dielectric constant were carried out for range (102-106) Hz frequency .The addition of Alumina filler exhibit slightly effect on values of dielectric constant for prepared ternary hybrid composite (PMMA-TiO2-Al2O3) compared with ZrO2 for ternary hybrid composite (PMMA-TiO2-ZrO2) which dielectric constant increase as concentration . Dissipation factor decrease with increasing frequency in composite of alumina and zirconia but in case the later yield good compatible. D.C electrical conductivity was conducted at temperature range (313-373) K. Markedly increasing of the D.C electrical conductivity for Zirconia filler respect to addition concentration and applied temperature.